The Efficacy and Safety of Sodium Bicarbonate Ringer’s Solution in Critically Ill Patients: A Retrospective Cohort Study - Bian, Yi; Xu, Tingting; Le, Yue; Li, Shusheng (Frontiers in Pharmacology, 2022)
Background: Sodium bicarbonate Ringer’s solution has been widely used in clinical practice in recent years. There are few clinical studies on the efficacy and safety of this fluid among critically ill patients until now. Method: This retrospective cohort study included critically ill adult patients in the intensive care unit of Tongji Hospital from January 1, 2019, to December 31, 2020. By reviewing exclusively use of either sodium bicarbonate Ringer’s solution or saline for resuscitation or maintenance, patients were included into two groups respectively. The primary outcome was the major adverse kidney event within 30 days (MAKE30), including death, new receipt of renal-replacement therapy or persistent renal dysfunction. Safety outcomes were focused on arterial blood gas and plasma biochemical alterations which might potentially be induced by the administration of bicarbonate Ringer’s solution. Result: A total of 662 patients were included in the cohort. Compared to the saline group, the bicarbonate Ringer’s group had a significantly lower rate of the new receipt of renal replacement therapy (adjusted OR = 0.591, 95% CI, 0.406 to 0.861; P = 0.006). There was no significant difference between the two groups in 30-day mortality, final creatinine level ≥ 200% of baseline and major adverse kidney event within 30 days. In subgroup analysis, the incidence of MAKE30 was higher in the bicarbonate Ringer’s group than that of the saline group among patients with cardiovascular disease. Patients in the bicarbonate Ringer’s group had a longer length of ICU stay compared to patients in the saline group, but their new renal replacement therapy days were shorter. No major alterations were found in arterial blood gas and plasma biochemical during the follow-up period. Conclusions: Compared to saline, sodium bicarbonate Ringer’s solution exhibited a potential renal function protective effect while causing no major alterations in arterial blood gas and plasma biochemical. However, the application in patients with cardiovascular disease diagnosis at ICU admission should be cautious.